THE MENTAL HEALTH OF ADOLESCENT REFUGEES IN MALAYSIA - Low, Sew Kim; Tan, Soon Aun; Kok, Jin Kuan; Nainee, Sarvarubini; Viapude, Glory Nancy (PEOPLE: International Journal of Social Sciences, 2018)
As of June 2017, 24.8 % of the 149, 200 reported refugees in Malaysia aged 18 years and below and of that figure, 33% were females. There has been little research into the mental well-being of the refugee adolescents. This cross-sectional survey study examined the differences in stress, anxiety, and depression faced according to gender and whether there is any association between them. 104 refugee adolescents from four non-governmental organization educational centers participated in the study. The Depression, Anxiety, Stress scale 21 was used to measure the severity of the core symptoms of depression. The results showed that females have significantly higher stress, anxiety and depression compared to that of males at p<.001. Generally,the refugee has mild to normal stress as compared with anxiety and depression where a significant majority of those aged 14-27 years experienced severe to extreme severe anxiety with a moderate level of depression. A further analysis found that severe stress positively associated with anxiety and depression. Insights into the stress, anxiety and depression experienced by refugee adolescents are crucial towards understanding the mental health of young refugees. The current study may benefit mental health workers and humanitarian agencies to address and improve the mental health of refugees, regardless of any labels attached to them.